Absence of Edge States in Covalently Bonded Zigzag Edges of Graphene on Ir(111) - Li, Yan; Subramaniam, Dinesh; Atodiresei, Nicolae; Lazić, Predrag; Caciuc, Vasile; Pauly, Christian; Georgi, Alexander; Busse, Carsten; Liebmann, Marcus; Blügel, Stefan; Pratzer, Marco; Morgenstern, Markus; et al. (Advanced materials (Weinheim), 2013)
The zigzag edges of graphene on Ir(111) are studied by ab initio simulations and low‐temperature scanning tunneling spectroscopy, providing information about their structural, electronic, and magnetic properties. No edge state is found to exist, which is explained in terms of the interplay between a strong geometrical relaxation at the edge and a hybridization of the d orbitals of Ir atoms with the graphene orbitals at the edge.